JUDGE’S LIABILITY WHILE CARRYING OUT THEIR PROFESSIONAL DUTIES - Marian ALEXANDRU (Challenges of the Knowledge Society)
Nowadays, the Romanian social and political context debates more and more on the patrimonial liability of judges for errors of law in cases settled by them. This work aims at presenting legal terms, based on which both the civil and criminal disciplinary liability can be generally enacted.